Social Accountability in Medical Education: Students’ Perspective - Masud, Nazish; Alenezi, Shahad; Alsayari, Ohoud; Alghaith, Deemah; Alshehri, Rana; Albarrak, Danah; Al-Nasser, Sami (Frontiers in Education, 2022)
Background Globally, there is a rising interest in the concept of social accountability (SA). The literature evaluating SA of medical schools is limited; however, some international studies have revealed a lack of understanding of SA by medical students. This study evaluated the perception of SA among medical students at a governmental university in Saudi Arabia. Method A cross-sectional study with 336 currently enrolled medical students was conducted from September 2020 to May 2021. The data were collected using an electronic survey comprised of the THEnet questionnaire that included 12 items to assess the perception of SA and some demographic variables. The total score was categorized into four groups and compared with the demographic profile of students. Results Out of the 336 participants, the mean age was 21.26 ± 0.5 years, with most students in the 19–21 age group (n = 154, 46%), and 189 (56.3%) were males. In addition, preclinical and clinical students had similar representation: 170 (51%) and 166 (49%), respectively. Most participants (173, 52%) scored in the 18–36 range, reflecting good perceived SA. The demographic profile of students (i.e., age, GPA, and year of study) was significantly associated with perceived SA (p = 0.003, 0.002, and < 0.001, respectively). Conclusion The study concludes that most medical students had a good level of perceived SA about their institution. The preclinical year students exhibited a better perception of SA. The final-year students were more critical about the SA of the institution compared to other students.